INOVASI LIMBAH WORTEL-MELATI UNTUK HARD SKILL KELOMPOK RELAWAN KEBERSIHAN PASAR - Lista, Lilis Septiani; Ali, Muhammad; Andi Muhammad Irfan Taufan Asfar; Akbar , Andi Muhamad Iqbal; Asdar, Muh; Sofiyan, Sofiyan (LPPM Universitas Bina Bangsa, 2025)
The problem of carrot waste in Balle Market, Palattae Village, Kahu District is a complex and urgent issue. The habit of people who only consume fresh carrots without utilizing half-damaged carrots causes the accumulation of carrot waste in the trash, which causes an unpleasant odor. Managing waste innovatively is important because it can support environmental sustainability. This Community Service activity aims to turn carrot and jasmine waste into Eco-enzyme Hand Sanitizer. The method applied is based on the active involvement of partners through counseling, training, and mentoring. The results of the program show a significant improvement in partner knowledge and skills, with an 80% increase in marketing knowledge. Awareness of the economic value of this waste also motivates partners to run businesses independently, which supports Sustainable Development Goal No. 12 on Responsible Consumption and Production. This implementation proves great potential in empowering the community through the effective use of waste